2010
DOI: 10.1177/0022034509353405
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Cot/Tp12 in Bone Loss during Periodontitis

Abstract: Periodontitis causes resorption of alveolar bone, in which RANKL induces osteoclastogenesis. The binding of lipopolysaccharide to Toll-like receptors causes phosphorylation of Cot/Tp12 to activate the MAPK cascade. Previous in vitro studies showed that Cot/Tp12 was essential for the induction of RANKL expression by lipopolysaccharide. In this study, we examined whether Cot/Tp12 deficiency reduced the progression of alveolar bone loss and osteoclastogenesis during experimental periodontitis. We found that the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…In summary, this study has shown that the role of MyD88 and Cot/Tpl2 in LPS‐induced chemokine expression in macrophages considerably varies depending on the kind of chemokine. Cot/Tpl2 in macrophages has been reported to regulate LPS‐induced cytokine expression in positive (TNF‐α and IL‐23) or negative (IL‐12) manner [18–21]. This present study further indicated that Cot/Tpl2 directly regulates transcription of various chemokines in LPS‐stimulated macrophages.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In summary, this study has shown that the role of MyD88 and Cot/Tpl2 in LPS‐induced chemokine expression in macrophages considerably varies depending on the kind of chemokine. Cot/Tpl2 in macrophages has been reported to regulate LPS‐induced cytokine expression in positive (TNF‐α and IL‐23) or negative (IL‐12) manner [18–21]. This present study further indicated that Cot/Tpl2 directly regulates transcription of various chemokines in LPS‐stimulated macrophages.…”
Section: Discussionsupporting
confidence: 74%
“…We and others have previously demonstrated that Cot/Tpl2 is indispensable for the LPS-induced activation of ERKs in macrophages, dendritic cells, and osteoblasts [16][17][18][19]. Lack of ERK activation in cot/tpl2 À/À macrophages results in impaired secretion of tumor necrosis factor (TNF) a and IL-23, along with the increased secretion of IL-12, in response to LPS [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…LPS signaling through pattern recognition receptors, such as Toll‐like receptor 4 (TLR4), triggers a cascade of intracellular events leading to the activation of intracellular transcription factors (e.g., nuclear factor κB), resulting in the production of proinflammatory cytokines 1 . LPS have been found to cause the breakdown of connective tissue and resorption of alveolar bone through the interaction with the host cells, including gingival fibroblasts 2,3 …”
mentioning
confidence: 99%
“…1 LPS have been found to cause the breakdown of connective tissue and resorption of alveolar bone through the interaction with the host cells, including gingival fibroblasts. 2,3 The fibroblast is the most abundant cell type in gingival connective tissues. Fibroblasts play a crucial role in maintaining, repairing, and remodeling of the extracellular matrix necessary for connective tissue homeostasis.…”
mentioning
confidence: 99%
“…As the levels of several inflammatory cytokines, including IL-1β [24] and TNF-α [25] are strongly increased in ligature-induced periodontitis in mice, as well in rats [26], we determined whether PTPα regulates inflammation-mediated destruction of periodontal tissues by placement of silk ligatures around the necks of molar teeth to induce periodontitis [27], [28] using wild type (PTPα +/+ ) or knock out (PTPα −/− ) mice. First the genotype of mice was confirmed by PCR analysis of tail clips using primers that recognize the insert in the null genotype.…”
Section: Resultsmentioning
confidence: 99%